Differences in feather structure between urban and forest great tits: constraint or adaptation? - Krisztina Sándor; Gábor Seress; Csenge Sinkovics; Áron Péter; András Liker (Journal of Avian Biology, 2022)
Urbanization is one of the strongest habitat transforming processes today that has resulted in changes in the ecological conditions for wild populations. In birds, the limitation of natural food sources and a warmer microclimate in cities can potentially influence the development and functioning of the plumage that may have important fitness consequences. Despite its potential significance, the plumage structure of urban birds are largely unexplored and it is unclear whether and how they respond to urban ecological processes such as different constraints and selection pressures. In this study, we compared several structural properties of contour, primary and tail feathers between two forest and two urban great tit Parus major populations. Our results show that the urban environment affects only a few structural properties of feathers and only in the plumage of first‐year birds. We found that both the plumulaceous and the pennaceous parts of their contour feathers are longer and have lower barb density in the urban than in the forest habitat. We also found that the primaries of first‐year birds have narrower rachis and higher barbule density in the cities than in the forests, but there were no differences in other wing feather traits and in any tail feather traits between habitats. We did not find differences in the feather structure of urban versus forest adult birds. The habitat differences in first‐year birds may indicate nutritional constraints or the effects of the warmer microclimate of the urban environment. These differences seem to disappear completely in adulthood that can be explained by the selective mortality of first‐year birds, or by adults being less sensitive than first‐year birds to environmental effects during their moult.